Mapping the research trend in the Web of Science on small-sided games in soccer: a Bibliometric study between 2010-2023 - Carlos Felipe Martínez Benítez; Boryi Becerra-Patiño; Diego Andrés Rada-Perdigon (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective. To examine the scientific production of Small-Sided Games in soccer in the period from January 01, 2010 to February 19, 2024, through the consideration of a bibliometric study in the Web Of Science database. Methodology. To select the documents, an analysis matrix was elaborated in Microsoft Excel based on 15 categories. A review based on PRISMA recommendations was carried out in the database (Web of Science). The VOSviewer program was used to create co-occurrence maps based on keywords, co-authorship, country, institutional affiliation and journals. Results. A total of 568 documents were obtained. The results show that the greatest production is generated in research articles (92.42%). For the publication period, a systematic increase is established from the year 2018, finding that the year 2021 was the year of highest production with 84 documents. The authors with the highest production are Clemente, F.M. (10.17%), Praça, G.M. (6.25%), Sampaio, J., and Gonçalves, B. (5.53%). Regarding the area of knowledge, the one with the highest production is Sports Sciences with 398 documents (70.07%). The journal that has published the most papers and, in turn, receives the most citations (3374) is the Journal of Strength and Conditioning Research (44 papers and 2141 citations). The journals with the highest number of citations are those in the Q1 quartile. The Polytechnic Institute of Viana do Castelo is the institution with the highest number of papers (66). The prevailing language in the scientific production is English (93.66%). Conclusions. Small-Sided Games are a reason for interest in Sport Sciences, and, especially it has been studied in greater depth since 2017, with Spain and Portugal being the countries that have generated the greatest production.